CONTROLLED RELEASE OF PHENYTOIN SODIUM FROM CASEIN MICROPARTICLES - VINO S; ABINAYA A; DIVYA V; GHOSH AR (International Journal of Pharma and Bio Sciences, 2014)
Casein is a biodegradable natural polymer with great potential for pharmaceutical applications due to its biocompatibility and non-toxicity. Microparticles carrier systems made from naturally occurring polymers based on casein system appears to be a promising carrier for the sustained release of orally and parenterally administered drugs. Casein microparticles are prepared by using microencapsulation technique. Phenytoin Sodium is used as a model drug which is loaded by the principle of steric stabilization and glutaraldehyde was used as a chemical cross-linking agent. The microparticles were prepared and characterized by X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), particle size analyzer and drug release studies were performed using simulated gastric and intestinal fluids. In this study it was demonstrated that casein microparticles loaded with Phenytoin sodium can be successfully prepared and these microparticulate systems seem to be quite promising for controlled release applications.